2018
DOI: 10.12688/f1000research.12239.1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoblastoma: current understanding, recent advances, and controversies

Abstract: Introduction: Hepatoblastoma (HB) is the most common primary malignant liver neoplasm in children. Its increasing survival rate is related to the progress in modern imaging, surgical techniques, and new chemotherapy regimens. Clinical approach: One of the past achievements was the development of the pretreatment extension of disease (PRETEXT) system. Gradually, the HB therapeutic approach has become more individualized with better stratification of patients. Controversies: These include the need for preoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 32 publications
3
56
0
2
Order By: Relevance
“…Many controversies about the treatment of hepatoblastoma still remain. Neoadjuvant chemotherapy combined with surgical treatment is the standard treatment method for hepatoblastoma, and surgical treatment is the basis of comprehensive treatment (12). However, studies have found that the volume of hepatoblastoma will decrease after neoadjuvant chemotherapy, but the distance between the tumor and the main blood vessels has not been significantly reduced (13).…”
Section: Discussionmentioning
confidence: 99%
“…Many controversies about the treatment of hepatoblastoma still remain. Neoadjuvant chemotherapy combined with surgical treatment is the standard treatment method for hepatoblastoma, and surgical treatment is the basis of comprehensive treatment (12). However, studies have found that the volume of hepatoblastoma will decrease after neoadjuvant chemotherapy, but the distance between the tumor and the main blood vessels has not been significantly reduced (13).…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, there is no consensus on the need of post–liver transplant chemotherapy for HB. There are some published studies with good results regardless of the use of post‐transplant chemotherapy . Also, some other centers recommend the use of post‐transplant chemotherapy to prevent tumor recurrence and improve the survival rate…”
Section: Discussionmentioning
confidence: 99%
“…There are some published studies with good results regardless of the use of post-transplant chemotherapy. 23,24 Also, some other centers recommend the use of posttransplant chemotherapy to prevent tumor recurrence and improve the survival rate. 25 We believe it is reasonable to express some concerns on the systematic use of post-transplant chemotherapy in every HB patients, even if they show a clear and sustained descent in post-transplant AFP levels.…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, the Wnt pathway is essential for homeostasis, embryogenesis, development, maturation, and regeneration [9]. It is also associated with several pathological conditions such as cirrhosis [10], hepatoblastoma [11,12], and hepatocellular carcinoma (HCC) [13]. Currently, several Wnt molecules with potential pharmacological value are being explored for future therapeutic interventions [14,15].…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%